4: Maintenance of threshing unit of your diesel-powered maize shelling machine. - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
A step by step guide on how a farmer can remove and repair or repalce thresher sieve if worn out. Repairs of the maize Sheller are required when unusual noise is detected on the machine. This should be done by disassembling some parts of the machine. This video was developed with funding from USAID through the Africa RISING Ghana project which is led by the International Institute of Tropical Agriculture (IITA). The purpose of the video is not to instantly turn farmers into specialist technicians, but to empower them to be able to perform basic maintenance activities when they don't have access to technicians.